2020
DOI: 10.3390/ijms21176043
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Diabetic Cardiomyopathy: The Possible Therapeutic Roles of Phenolic Acids

Abstract: As the powerhouse of the cells, mitochondria play a very important role in ensuring that cells continue to function. Mitochondrial dysfunction is one of the main factors contributing to the development of cardiomyopathy in diabetes mellitus. In early development of diabetic cardiomyopathy (DCM), patients present with myocardial fibrosis, dysfunctional remodeling and diastolic dysfunction, which later develop into systolic dysfunction and eventually heart failure. Cardiac mitochondrial dysfunction has been impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 175 publications
(112 reference statements)
0
22
0
Order By: Relevance
“…Reduction in cardiomyocyte population is caused by extensive cardiomyocyte death resulting from oxidative damage and apoptosis is induced by chronic hyperglycemia. Due to this, viable cardiomyocytes have to bear the burden to generate enough force in order to pump blood from and into the heart, subsequently causing the cells to enlarge, known as the pathological hypertrophy [25,26]. the dead cardiomyocytes, and the stiff nature of collagen tissue causes the heart to lose its contractility and flexibility [27].…”
Section: Diabetic Cardiomyopathy: Understanding the Cardiac Oxidative Stress Inflammation And Apoptosis-related Pathophysiology And Pathomentioning
confidence: 99%
“…Reduction in cardiomyocyte population is caused by extensive cardiomyocyte death resulting from oxidative damage and apoptosis is induced by chronic hyperglycemia. Due to this, viable cardiomyocytes have to bear the burden to generate enough force in order to pump blood from and into the heart, subsequently causing the cells to enlarge, known as the pathological hypertrophy [25,26]. the dead cardiomyocytes, and the stiff nature of collagen tissue causes the heart to lose its contractility and flexibility [27].…”
Section: Diabetic Cardiomyopathy: Understanding the Cardiac Oxidative Stress Inflammation And Apoptosis-related Pathophysiology And Pathomentioning
confidence: 99%
“…The heart is an organ with high energy demand, largely dependent on the function of mitochondria, which provide approximately 90% energy and are a major source of reactive oxygen species (ROS) [ 5 ]. Increased mitochondrial ROS production and resultant mitochondrial dysfunction are generally recognized to play a pivotal role in the development of DCM [ 6 , 7 ]. Recently, it has been highlighted that imbalanced mitochondrial fusion/fission dynamics is an early component that increases mitochondrial ROS production and induces mitochondrial dysfunction [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have indicated that uncontrolled inflammation and oxidative stress may contribute to cardiac dysfunction in diabetic cardiac tissues (10,11). Extensive research has also revealed that mitochondrial injury may serve as a central mediator in the pathology of DCM (12,13). Therefore, identifying potential therapeutic strategies that target chronic inflammation and oxidative stress may aid in the management of DCM.…”
Section: Introductionmentioning
confidence: 99%